If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + 15 = 11 + 5x Reorder the terms: 15 + 3x = 11 + 5x Solving 15 + 3x = 11 + 5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5x' to each side of the equation. 15 + 3x + -5x = 11 + 5x + -5x Combine like terms: 3x + -5x = -2x 15 + -2x = 11 + 5x + -5x Combine like terms: 5x + -5x = 0 15 + -2x = 11 + 0 15 + -2x = 11 Add '-15' to each side of the equation. 15 + -15 + -2x = 11 + -15 Combine like terms: 15 + -15 = 0 0 + -2x = 11 + -15 -2x = 11 + -15 Combine like terms: 11 + -15 = -4 -2x = -4 Divide each side by '-2'. x = 2 Simplifying x = 2
| -7x+16=8(5x+2) | | -8p=176 | | 4(x+2)/6 | | 3+5(-8a-1)=-6-(3a-4) | | 0.15-0.01(x+1)=-0.03(2-x) | | (-2x/11)=66 | | 7x+3=2(3x+1)-x+8 | | x+6=15-x | | 13/6+x=6 | | 16n^2-8n-15=0 | | 2x-5y=4x+15 | | 5/2x=3/2x-4 | | 35x^4-2x^2-1=0 | | 14w-18=94 | | 9(x+6)+5=59 | | -533-(-276)= | | -2(-6k-5)=-15+7k | | -x+3+11x=-3+4x+48 | | .5x+.05x=256 | | 4(5k-5)+19=-9+2(3k-8) | | 13+3(2x-5)=1-2(3-6x) | | 3c-1c+40=34 | | 4/3+2=6 | | x+2x+13=70 | | 7.5-(-2.5)= | | a(c-2)+3(c-2)= | | 92=-8+25m | | x+.05x=23.63 | | -(5+2x)=2(3+4x) | | 5t-14=8t+4 | | 3(n-5)=9-n | | 2x+4=-1(7x+6) |